The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1007/bf00410109
|View full text |Cite
|
Sign up to set email alerts
|

CEA (carcinoembryonic antigen): Its role as a marker in the management of cancer

Abstract: A consensus Development Conference was held at the National Institutes of Health from September 29-October 1, 1980, to address issues concerning the role of carcinoembryonic antigen (CEA) as a marker in the management of cancer. The panel met following formal presentations and discussions to assess the issues based on the evidence presented. These issues included: Should CEA be used in cancer screening? Is CEA helpful in cancer diagnosis? What does CEA tell about the extent and outcome of cancer? Is CEA helpfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In an earlier study, we coupled p-[1,2-dicarba-closo- [ (10), and found that boron labeling did not destroy the immunoreactivity of the antibodies labeled with eight carborane cages or less (11). It was the objective of the current study to assess the tumorlocalizing capabilities of such boron-conjugated antibodies against CEA.…”
mentioning
confidence: 89%
“…In an earlier study, we coupled p-[1,2-dicarba-closo- [ (10), and found that boron labeling did not destroy the immunoreactivity of the antibodies labeled with eight carborane cages or less (11). It was the objective of the current study to assess the tumorlocalizing capabilities of such boron-conjugated antibodies against CEA.…”
mentioning
confidence: 89%
“…Development of sensitive, specific immunoassays to detect circulating tumor-shed antigens can assist in the early detection of the disease, at a stage more likely to yield to therapeutic procedures (Goldenberg et a/., 1981;Chu, 1990). Radiolabeled antibodies have been shown to be of considerable value for the clinical localization of tumor masses (Colcher et a/., 1987;Goldenberg et al, 1989).…”
mentioning
confidence: 98%
“…Tumour antigen levels have been used for many years in the clinical management of cancer (Goldenberg et al, 1981). They have proved of value in detecting recurrent disease (NIH Consensus Statement, 1981;Hida et al, 1996), monitoring the effects of chemotherapy and predicting prolonged survival (Hine and Dykes, 1984;AllenMersh et al, 1987;Ward et al, 1993).…”
mentioning
confidence: 99%